Alpha-actinin-3 R577X polymorphism influences muscle damage and hormonal responses after a soccer game - Coelho, D. B.; Pimenta, E. M.; Rosse, I. C.; Veneroso, C.; Pussieldi, G. D. A.; Becker, L. K.; De Oliveira, E. C.; Carvalho, M. R. S.; Silami-Garcia, E. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to evaluate indicators of muscle damage and hormonal responses after soccer matches and its relation to alpha-actinin-3 (ACTN3) gene expression (XX vs. RR/RX), considering that the R allele produces alpha-actinin-3 and provides greater muscle strength and power. Thirty players (10 XX and 20 RR/RX) younger than 16 years were evaluated in this study. Blood samples were collected immediately before, after, 2, and 4 hours after the games to assess muscle damage (creatine kinase [CK] and alpha-actin) and hormonal responses (interleukin-6 [IL-6], cortisol, and testosterone). Postgame CK was higher as compared to the pregame values in both groups and it was also higher in the RR/RX (p < 0.05) than in the XX. The concentrations of alpha-actin and IL-6 were similar for both groups and did not change over time. Testosterone was increased after the game only in the RR/RX group (p < 0.05). Cortisol concentrations in group RR/RX were higher immediately after the game than before the game, and 2 and 4 hours after the game the concentration decreased (p < 0.05). The RR and RX individuals presented higher markers of muscle microtrauma and hormonal stress, probably because they performed more speed and power actions during the game, which is a self-regulated activity. From the different responses presented by RR/RX and XX genotypes, we conclude that the genotypic profile should be taken into account when planning training workloads and recovery of athletes.